Learning love from a tiger : religious experiences with nature - Capper, Daniel, 1962- (University of California Press, 2016)
"Learning Love from a Tiger explores the vibrancy and variety of humans' sacred encounters with the natural world, gathering a range of stories culled from Christian, Muslim, Hindu, Mayan, Himalayan, Buddhist, and Chinese shamanic traditions. Readers will delight in tales of house cats who teach monks how to meditate, rivers that grant salvation, shamans who shape-shift into jaguars, crickets who perform Catholic mass, and many others. More than a collection of wonderful stories, this book introduces important concepts and approaches that underlie much recent work in environmental ethics, religion, and ecology. Capper's light touch prompts readers to engage their own views of humanity's place in the natural world and in particular question longstanding assumptions of human superiority"--Provided by publisher